Scroll Culture, Fragmentasi Atensi, dan Krisis Kontemplasi: Suatu Tinjauan Teologis terhadap Spiritualitas Digital - Chris Sorongan; Yosep Heristyo; Imanuel Widjaja (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2026)
The development of digital culture has given rise to scroll culture as a pattern of information consumption that shapes modern human attention through rapid and continuous streams of digital stimuli. This study aims to analyze the relationship between scroll culture, attention fragmentation, and the crisis of contemplation from the perspective of Christian theology. The research employs a qualitative method using a library research approach through an interdisciplinary analysis of media theory, digital culture, and Christian spirituality. The findings indicate that scrolling culture, shaped by the mechanisms of the attention economy, drives individuals toward fragmented, accelerated, and distracted patterns of attention. This condition not only affects human cognitive patterns but also weakens the capacity for reflection, silence, and spiritual contemplation. From a theological perspective, attention is understood as a spiritual dimension related to humanity's relationship with God. Therefore, attention fragmentation in the digital era can be understood as a form of spiritual crisis in contemporary human life. This study also demonstrates that scroll culture may be understood as a form of "digital liturgy" that shapes human attentional habits through repetitive scrolling practices. In response to this condition, contemplative spirituality is regarded as essential for restoring attention, silence, and relational depth amid a culture of digital distraction.